Novel Alkynylphosphonate Analogue of Calcitriol with Potent Antiproliferative Effects in Cancer Cells and Lack of Calcemic Activity - Salomón, Débora Gisele (2011)
Here, we describe the design and synthesis of diethyl [(5Z,7E)-(1S,3R)-1,3- dihydroxy-9,10-secochola-5,7,10(19)-trien-23-in-24-yl] phosphonate (compound 10), which combines the low calcemic properties of phosphonates with the decreased metabolic inactivation due to the presence of a triple bond in C-24 and studied its in vitro effects on several cancer cell lines and its in vivo effects on blood calcium levels. We demonstrate that this compound is a potent antiproliferative vitamin D analogue, showing lack of calcemic effects in vivo.